Sistem Pendukung Keputusan Kenaikan Jabatan Karyawan PT. Indomarco Prismatama Menggunakan Metode Simple Multi-Ttribute Rating Technique - Ahmad Febri Hartanto; Putri Dina Mardika (Universitas Indraprasta PGRI, 2022)
The promotion of employees at PT Indomarco Prismatama is still done manually, so it is possible if decision making is done subjectively by only looking at certain aspects. weights that have been determined by the company. The method used in decision making is the SMART method, with this method we can find out which employees are included in the weights and criteria for promotion at PT Indomarco Prismatama. The existence of problems at PT Indomarco Prismatama requires a Decision Support System in determining employee promotions. The system development method uses quantitative and qualitative models as well as the PHP programming language, native php and MySQL database. The final result in this research is the establishment of a Decision Support System for Employee Promotion at PT Indomarco Prismatama. With this website-based SMART method, it can determine which employees are worthy of consideration and have not been selected to choose the best one in occupying the position. After the decisions obtained in the decision support system application, the system will display the results of the decisions that have been taken.Keyword : Decision Support System, SMART Method (Simple Multi Attribute Rating Technique), Quantitative and Qualitative Method